2018
DOI: 10.1111/bjd.16894
|View full text |Cite
|
Sign up to set email alerts
|

Stop routine screening for associated malignancies in cutaneous noninvasive vulvar Paget disease?

Abstract: Of our patients with VPD, 76·9% were diagnosed with cutaneous noninvasive VPD, and this group has no increased risk for developing malignancies of the breast, intestine or urological tract. Our study suggests that routine screening for these malignancies in patients diagnosed with cutaneous noninvasive VPD may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
2
8
1
Order By: Relevance
“…Common sites of the associated malignancies were the colon, rectum, prostate, and bladder; therefore, consideration of screening for internal malignancies might be required when EMPD is diagnosed. However, a recent population study with age-matched control showed no increased risk of associated malignancies in noninvasive primary vulvar EMPD patients, indicating that risk of other malignancies have been overestimated in large elderly population of EMPD patients [89,90]. From this finding, the authors suggest that routine screening for other malignancies in patients diagnosed with primary noninvasive vulvar EMPD may not be needed.…”
Section: Patient Evaluationmentioning
confidence: 90%
“…Common sites of the associated malignancies were the colon, rectum, prostate, and bladder; therefore, consideration of screening for internal malignancies might be required when EMPD is diagnosed. However, a recent population study with age-matched control showed no increased risk of associated malignancies in noninvasive primary vulvar EMPD patients, indicating that risk of other malignancies have been overestimated in large elderly population of EMPD patients [89,90]. From this finding, the authors suggest that routine screening for other malignancies in patients diagnosed with primary noninvasive vulvar EMPD may not be needed.…”
Section: Patient Evaluationmentioning
confidence: 90%
“…Although the rate of local recurrence is high in all patients with EMPD (approximately 40%), the risk of other malignancies is limited to patients with invasive disease (8% of cases) and patients with secondary EMPD [8][9][10]. Most cases of EMPD are primary and non-invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical analysis may aid in identifying secondary EMPD. Primary lesions are CK7+/CK20-; lesions with intestinal phenotype are CK7 −/CK20+/CDX2+; lesions with urothelial phenotype are CK7+/CK20+/uroplakin+ [8]. EMPD of urothelial origin is the rarest type of secondary EMPD, and urothelial neoplasia can appear before or up to 13 yr after the onset of vulvar symptoms [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent study by Van der Linden [1], however, secondary EMPD does not increase the risk of malignancy compared with the general population. Up until now, not so many familial EMPD cases have been reported.…”
Section: Introductionmentioning
confidence: 94%